1023 An Audit of The Prevalence of Frailty and The Impact on Surgical Management and Resource Use, For Vascular Inpatients Using the National Vascular Registry (NVR) Frailty Classifications. (12th October 2021) - Hitchman, L; Palmer, J; Sethi, S; Chetter, I
Abstract: Aim: To determine if the NVR frailty score was being routinely collected on all relevant vascular patients on admission, identify the prevalence of frailty in vascular inpatients and determine if frailty was associated with a higher mortality and morbidity. Method: A prospective audit of consecutive patients admitted onto the vascular ward who were eligible for inclusion on the NVR. Data was collected from electronic patient records and paper case notes between November 2019 and February 2020. The primary outcome was completeness of frailty assessment. Secondary outcomes were prevalence of frailty and mortality and morbidity associated with frailty score. Results: Frailty status was documented in 65% of patients. 43% (28/65) were assessed to be frail. The 30-day mortality rate was 1.53% (1/65). 26.15% (17/65) had one or more complication. The commonest complications were graft occlusions, acute kidney injury, hospital acquired pneumonia and groin infections. 93.84% (61/65) were discharged home. There was no correlation between frailty and number of post-operative complications (p = 0.394), length of stay (p = 0.171) or mortality (p = 0.371). Conclusions: This audit found frailty assessment is poorly assessed and the current NVR frailty classification did not correlate to increase mortality or morbidity in this patient cohort.